AN APPROACH FOR AGE ESTIMATION WITH INCREMENTAL LINES FROM ROOT CEMENTUM OF HUMAN TEETH WITH LIGHT MICROSCOPE IN NORTH INDIAN POPULATION - Dr. Neha Upadhyaya; Dr. Rohit Sharma; Dr. M.K. Sunil; Dr. Rakesh Kumar Mishra; Dr. Akansha Srivastava (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Forensic age estimation plays one of the essential roles in the unknown human remains identification. Like in mass disasters and criminal investigations cases. Out of various odontological methods, analysis of incremental lines in root cementum has emerged as a non-destructive and reliable approach. Cementum, a mineralized avascular tissue covering the tooth root, continuously deposits throughout life in the form of alternating light and dark concentric bands, known as incremental lines or cemental annulations. This study explores the use of light microscopy to analyze these incremental lines for age estimation in the North Indian population. Ground sections of extracted teeth were prepared and examined under a light microscope to count the cemental annulations. The estimated age was then calculated by adding the eruption age of the respective tooth to the number of observed cemental lines. This method showed promising correlation between chronological and estimated age, supporting its validity and applicability in forensic contexts. The study reinforces the scientific rigor of cementum-based age estimation as a reliable adjunct in forensic odontology.